Moral Values In Mamaos Cianjuran As A Local Identity At The Literacy Program - Yuki, Librilianti Kurnia; Novi Anoegrajekti; Ninuk Lustyantie (Pujangga : Jurnal Bahasa dan Sastra, 2024)
Years of critical discourse analysis research on Mamaos Cianjuran as a local identity have been carried out by researchers. Mamaos is reading a beautiful kind of Sundanese poetry in the form of prayers that are sung. Mamaos is a local wisdom in Sundanese songs in West Java. The existence of the phenomenon of Mamaos Cianjuran will be revitalized by adjusting the content of the Mamaos Cianjuran song verses to the current generation Z which can cause a new problem, namely loss of rules of Mamaos in the form of prayer (rajah) as one of the new problems. This qualitative research was conducted using critical discourse analysis methods. One of the titles of mamaos Cianjuran studied is Papatet. There are various types of papatets including queen papatet. Papatet Ratu is the name of the Cianjuran mamaos song which is commonly used as a song with beautiful verses in the form of prayers (rajah in Sundanese) which are chanted in songs in an event to give glory to a mother. The results of the study in the form of representations of moral values contained in Cianjuran as a local identity should not leave the pacem let alone eliminate it, because it represents moral values in human relations with God, humans with humans, and humans with the surrounding environment which are implemented as literacy programs by the Government.